2019
DOI: 10.1126/sciadv.aaw7414
|View full text |Cite
|
Sign up to set email alerts
|

Structure and genome ejection mechanism of Staphylococcus aureus phage P68

Abstract: Cryo-EM reveals the genome ejection mechanism of bacteriophage P68, a potential phage therapy agent against Staphylococcus aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 60 publications
0
40
1
Order By: Relevance
“…The structure of RBP is remarkably similar to the "tail fiber" (gp17) of the distantly related staphylococcal podovirus P68 [37] (Fig 5C, S1 Table), presumably reflecting specificity for S. aureus surface structures. However, in P68 gp17, the stem domain is less bent at the hinge compared to 80α (66˚vs.…”
Section: Receptor Binding Protein (Rbp Gp61)mentioning
confidence: 77%
See 2 more Smart Citations
“…The structure of RBP is remarkably similar to the "tail fiber" (gp17) of the distantly related staphylococcal podovirus P68 [37] (Fig 5C, S1 Table), presumably reflecting specificity for S. aureus surface structures. However, in P68 gp17, the stem domain is less bent at the hinge compared to 80α (66˚vs.…”
Section: Receptor Binding Protein (Rbp Gp61)mentioning
confidence: 77%
“…Host specificity is reflected in the structure of the receptor-binding structures of the infecting phages. The distantly related S. aureus-infecting podovirus P68 has a "tail fiber" protein (gp17) that is remarkably similar to the 80α RBP [37] (25% sequence identity), suggesting that this structure is conserved among phages that infect S. aureus. In contrast, phage Andhra, which is structurally very similar to P68, but infects S. epidermidis [40], has a completely different predicted RBP structure based on a β-helical architecture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NATURE COMMUNICATIONS | https://doi.org/10.1038/s41467-020-15575-4 ARTICLE Analysis of the recently published, in situ 12-fold-averaged cryo-EM reconstructions of the portals of phages phi29 16 , P23-45 17 , P68 44 , and herpes simplex virus 1 15 , suggests that the portal morphing likely occurs in many other viruses. Because of the 12fold averaging, these reconstructions can resolve only those parts of the portal structure, which obey the 12-fold symmetry, whereas the symmetry-mismatched capsid-portal interface is not resolved.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the N-terminal portal regions are not resolved in all these reconstructions. Also, in the P68 portal 44 , there is the long unresolved loop formed by residues 84-103, located in the periphery of the wing domain. Since these unresolved portal regions do not obey the 12-fold symmetry, they probably interact with the capsid and morph to compensate for the symmetry mismatch.…”
Section: Discussionmentioning
confidence: 99%